Evaluation of human epididymal secretory protein 4 expression according to the molecular subtypes (luminal A, luminal B, human epidermal growth factor receptor 2-positive, triple-negative) of breast cancer - Gamze Akoz; Gulden Diniz; Sumeyye Ekmekci; Zubeyde Yildirim Ekin; Melek Uncel (Wolters Kluwer Medknow Publications, 2018)
Background/Aims: Human epididymal secretory protein 4 (HE4) is originally described as an epididymis-specific protein but more recently suggested to be a putative serum tumor marker for some tumors, including breast carcinomas. In this study, we aimed to investigate the interactions between HE4 expression and molecular subtypes of breast carcinomas. Methods: HE4 expressions were studied in 242 formalin-fixed, paraffin-embedded breast carcinoma specimens and their association with different pathological and clinical parameters was evaluated. Results: Immunohistochemical (IHC) staining for HE4 was negative in 3 (1.2%) cases, weakly positive (1+) in 7 (2.9%) cases, moderately positive (2+) in 58 (24.0%) cases, and strongly positive (3+) in 174 (71.9%) cases. A correlation between IHC HE4 staining grade and molecular groups was detected (P = 0.005). Furthermore, it was found that HE4 expression was strongly associated with histological tumor grade, c-erbB2 expression, and positive fluorescence in situ hybridization test results that detect human epidermal growth factor receptor 2 (HER2)/neu amplification (P = 0.022, P = 0.014, and P = 0.011). Conclusion: This study showed that HE4 expression is associated with HER2/neu amplification in breast cancers. These results may be commented as HE4 expression rises in patients with HER2/neu amplification. As is known, HER2/neu amplification is a poor diagnostic factor in breast cancer and HE4 expression is possibly associated with poor prognosis.